The Sustainability of Fiscal Policy and Deficit Budget Financing : Evidence from Selected Muslim Countries - Muhammad Zilal Hamzah; Abd. Ghafar b. Ismail (Universitas Islam Indonesia, 2005)
The sustainability of fiscal policy and how to finance the deficit budget has been receiving increasing attention from economists. The issue is paramount for the Muslim Countries and this is one of the motivations of the paper. In order to assess the sustainability of budget deficits in selected Muslim countries, a descriptive statistics for the stock of revenue, expenditure, tax over GDP and sustainability tests of government debt and deficit are performed for the Muslim countries for the 1971-2000 period. The cointegration model is also used to test the relationship between government expenditures, taxes, and seigniorage. The results show that the Muslim countries use taxes and seigniorage to finance their government expenditures. The empirical results also allow us to conclude that fiscal policy may be sustainable for most Muslim countries. JEL classification: E60; H62; H63;Keywords: deficit finance; inter-temporal budget constraint; fiscal policy; monetary policy; islamic countries.